Roti Hidup dalam Injil Yohanes: Simbolik-Sakramental tentang Pewahyuan Kristus dan Ekaristi - Amandus Suhaedi Dol; Laurentius Prasetyo; Yanto Sandy Tjang (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The study examines the symbolic meaning of the “Bread of Life” in John 6 through an exegetical-theological approach, using intertextual and narrative-semiotic perspectives. It uncovers the dynamics of Johannine Christological revelation, which moves from miracle as sign, through theological discourse, and culminates in the sacramental understanding of the Eucharist. The Gospel of John is read as a text that employs symbolism and patterns of misunderstanding to lead readers from a literal reading toward deeper faith in Jesus as the source of true life. In this framework, the “Bread of Life” functions not merely as metaphor but as a revelatory symbol integrating Christological, soteriological, and ecclesiological dimensions. Findings show that this symbol is rooted in Old Testament motifs such as manna, Exodus, and wisdom, reinterpreted Christologically in Jesus. The feeding miracle points beyond physical sustenance to divine revelation, culminating in the statement “I am the Bread of Life.” John 6:51b–58 intensifies this sacramental meaning, forming the basis for Eucharistic theology, where participation in Christ’s body and blood signifies existential communion with God. The study concludes that John integrates Christology and sacramental theology, portraying faith as movement from sign to reality, recognition to participation, and revelation to communion with Christ.